2020
DOI: 10.1111/1745-9133.12529
|View full text |Cite
|
Sign up to set email alerts
|

Sentencing scorecards: Reducing racial disparities in prison sentences at their source

Abstract: Scorecards have become an increasingly common tool for public policy decision making about important issues in education, finance, and health care. Few scorecards have been applied in criminal justice and none has been developed to highlight racial disparities in incarceration. We constructed county-level scorecards for racial disparities in incarceration rates for the New York State Permanent Commission on Sentencing. Using detailed data on felony cases in New York State between 2000 and 2014, including the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…extend previous work that, irrespective of race, identifies substantial inter-jurisdictional discrepancies in sentencing outcomes within state systems (Ridgeway et al, 2020;Wright, 2012) and the federal system (Harries and Lura, 1973;United States Sentencing Commission, 2020a;Wu and Spohn, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…extend previous work that, irrespective of race, identifies substantial inter-jurisdictional discrepancies in sentencing outcomes within state systems (Ridgeway et al, 2020;Wright, 2012) and the federal system (Harries and Lura, 1973;United States Sentencing Commission, 2020a;Wu and Spohn, 2010).…”
Section: Discussionsupporting
confidence: 74%
“…We observed demographic differences in rural and urban courts, along with rural courts sentencing defendants with straddle cell cases to prison more often. Similarly, prior research in Michigan has shown wide variation in sentences received within individual grid cells across counties (Council of State Governments Justice Center, 2014; see Ridgeway et al., 2020, for an analysis of county‐level variation in punishment in New York). Yet we are not able to explore the possible theoretical mechanisms through which informal consequences operate differently in different court contexts.…”
Section: Discussionmentioning
confidence: 88%
“…Note, however, that our results therefore likely provide conservative estimates of the effects explored. We encourage future scholarship on this topic to employ alternative methods that can better account for some of these issues (e.g., MacDonald and Donnelly 2019; Ridgeway et al 2020).…”
Section: Discussionmentioning
confidence: 99%